Concomitant Obstructive Sleep Apnoea in Patients with Meniere’s Disease: A Case Report and Literature Review - Low, Wong Kein; Lim, Esther Jiayi (Case Reports in Otolaryngology, 2021)
Meniere’s disease (MD) is a condition characterised by fluctuating and progressive hearing loss, aural fullness, tinnitus, and intermittent attacks of vertigo. The disabling vertigo symptoms can be controlled in most patients by lifestyle changes and medications such as diuretics. Should standard medical therapy fail, the patient may require surgery in order to control the disease, but such surgical procedures can be functionally destructive. Obstructive sleep apnoea syndrome (OSAS) is common, especially in people who are grossly overweight. Up to 15% of patients with MD may have concomitant OSA. Unless the OSA is well controlled, such patients may continue to experience MD symptoms despite receiving adequate standard medical therapy for MD. Moreover, MD patients may experience insomnia as a result of vertigo and/or tinnitus where sedatives are indicated. The use of sedatives with muscle relaxant properties may inadvertently further aggravate OSA resulting in a vicious cycle of symptoms. Symptoms suggestive of concomitant OSA must be proactively sought as these patients do not necessarily exhibit the obvious phenotypic features of OSA. This is especially so in Asians where OSAS is commonly observed in people who are not overly obese. We report a case of a female patient who presented with recalcitrant MD disease and was later found to have concomitant OSA. The relevant literature will be reviewed, and learning points will be discussed from the perspective of the otologist/neurotologist. The clinician must always be mindful of the existence of concomitant “silent” OSAS as this impacts the management of patients with MD.